Blue Light Inhibits E. coli, but Decisive Parameters Remain Hidden in the Dark: Systematic Review and Meta-Analysis - Lawrence, Connor; Waechter, Sebastian; Alsanius, Beatrix W. (Frontiers in Microbiology, 2022)
Blue light (400–500 nm) alleviates overexposure risks associated to UV light and has therefore gained increased interest in multiple applications. This meta-analysis deals with decontamination of E. coli through the use of blue light based from nine recent publications identified via a systematic literature search. In these studies, various pathogenic and non-pathogenic E. coli strains grown in nutritional broths were exposed to wavelengths ranging from 395 to 460 nm. Five meta-analyses were performed using Cochrane’s software for meta-analyses (Review Manager): one including all studies to estimate the effect of E. coli reduction and four subgroup-analyses considering reported intensities, wavelengths, exposure dose as well as serovars/pathovars. Random effects models were used. All included studies used colony-forming units to estimate the impact of E. coli reduction. None of the included studies involved an organic matrix (e.g., skin, food related surface). Exposure to blue light had a significant and large reducing effect on viable counts of E. coli. However, substantial heterogeneity across studies was observed. Among subgroups, reported intensity and wavelength showed the clearest impact on E. coli reduction. With respect to the reported exposure dose, the picture across the spectrum was scattered, but effect sizes tend to increase with increasing exposure dose. Substantial heterogeneity was also present with respect to all serovar/pathovar subgroups among the included studies. The present body of reports does not display a strong basis for recommendation of relevant intensities, wavelengths and exposure doses for superficial blue light decontamination in medical or food safety contexts. A serious shortcoming in most studies is the absence of a clear documentation of inoculum preparation and of study parameters. We suggest improvement for study protocols for future investigations.